Polarization and Electromagnetic Emissions of Natural Crystalline Structures upon Acoustic Excitation; Materials Science Forum; Vol. 970 : Modern Problems in Materials Processing, Manufacturing, Testing and Quality Assurance II - Bespalko A. A. Anatoly Alekseevich; Surzhikov A. P. Anatoly Petrovich; Fedotov P. I. Pavel Ivanovich; Pomishin E. K. Evgeny Karlovich; Stary O. Oldrich (2019, 2019)
Title screen